How do Export Risk Guarantees affect Exports? The Case of Switzerland - Nils Herger; Michael Lobsiger (Aussenwirtschaft, 2010)
For the case of Switzerland, this paper endeavours to uncover in how far officially backed guarantees on trade finance achieve their stipulated goal of promoting exports.The results of gravity equations suggest that the Swiss Export Risk Insurance scheme increases exports in the manufacturing sector by around 1 per cent.As regards specific destination countries and industries, this average increase is highly concentrated and accrues primarily with exports towards large emerging markets and of chemical products as well as machinery.
Keywords: F13; 330